Model of restorative justice in the colombian State: approaches to differentiate it from the retributive model of justice in the accusatory process - Lozano Parra, Johan Sebastián; Caballero Palomino, Sergio Andrés; Jaimes Melgarejo, María Fernanda; Rincón Remolina, Érika Patricia (DIXI, 2023)
The purpose of this article is to analyze the model of restorative justice within the Colombian State and the elements that compose it, starting from the substantial difference that may exist in the retributive model and the constitutional jurisprudence. The generalized concept of restorative justice is studied with respect to its incidence in praxis. The main results of the analytical study allowed the generation of a theoretical and legal basis on the model studied, whose conclusions are aimed at explaining how restorative justice provides the basis for a true procedural materialization of the victims and persons involved in a judicial proceeding. At the same time, it is found that the model itself is a legal framework that has its own bases and normative development within the Colombian State, as well as a unique and specific jurisprudential basis.
Keywords: rule of law; restorative justice; retributive justice; mediation; criminal process; conciliation